2010
DOI: 10.4315/0362-028x-73.12.2211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slightly Acidic Electrolyzed Water for InactivatingEscherichia coliO157:H7 andStaphylococcus aureusAnalyzed by Transmission Electron Microscopy

Abstract: The use of different available chlorine concentrations (ACCs) of slightly acidic electrolyzed water (SAEW; 0.5 to 30 mg/liter), different treatment times, and different temperatures for inactivating Escherichia coli O157:H7 and Staphylococcus aureus was evaluated. The morphology of both pathogens also was analyzed with transmission electron microscopy. A 3-min treatment with SAEW (pH 6.0 to 6.5) at ACCs of 2 mg/liter for E. coli O157:H7 and 8 mg/liter for S. aureus resulted in 100% inactivation of two cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…In their study using electrolyzed oxidizing water (pH 2.5, ORP of 1,150 mV, residual chlorine of 60 mg/liter), Liao et al (14) also reported a disruption of E. coli cellular membrane and attributed this damage to the high ORP. Nan et al (22) used slightly acidic electrolyzed water (electrolysis of a mixture of NaCl and HC1, resulting in water with a pH of 6.2 to 6.3, an ORP of 849 to 857 mV, and an RCL of 10 to 30 mg/liter) to treat E. coli and documented similar disruption of the cellular membrane, as observed for Salmonella in this study.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In their study using electrolyzed oxidizing water (pH 2.5, ORP of 1,150 mV, residual chlorine of 60 mg/liter), Liao et al (14) also reported a disruption of E. coli cellular membrane and attributed this damage to the high ORP. Nan et al (22) used slightly acidic electrolyzed water (electrolysis of a mixture of NaCl and HC1, resulting in water with a pH of 6.2 to 6.3, an ORP of 849 to 857 mV, and an RCL of 10 to 30 mg/liter) to treat E. coli and documented similar disruption of the cellular membrane, as observed for Salmonella in this study.…”
Section: Resultssupporting
confidence: 73%
“…2B), when compared with the Salmonella cells treated with anolyte. Previous reports showed that another gram positive bacterium, S. aureus, was not as sensitive as E. coli when treated with NaCl (7) or slightly acidic (6.2 to 6.3) EW (22). However, in this study the morphological effects of the anolyte-treated L. monocytogenes exhibited some disruption of the outer cellular membrane (Fig.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…Each bacterium was hydrated according to manufacturer's directions and cultured in tryptic soy broth supplemented with 0.6% (w/v) yeast extract (TSBYE, CVCC, Beijing, China) at 37℃ for 24 h. Cells of each culture were separately centrifuged at 3,000×g for 10 min at 4℃ (3K15, Sigma, Germany) and the supernatants were discarded. The cell pellets were washed twice with 0.1% peptone water and then re-suspended in 10 mL of the same solution (Nan et al, 2010 solution was diluted in sterile deionized water to obtain the same ACCs with SAEW. Sodium hypochlorite (NaClO) solution was prepared by diluting 8% NaClO solution using deionized water to obtain the final different concentrations, and deionized water was used as control for this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The antimicrobial effect of SAEW has been proved and its application is widely accepted as an environmentally friendly sanitization method (5,6). SAEW is generated based on electrolysis of a dilute hydrochloric acid (HCl) and/or NaCl solution in an electrolytic chamber without a membrane (7).…”
Section: Introductionmentioning
confidence: 99%